Pengaruh Komite Audit, Dewan Komisaris, dan Dewan Direksi Terhadap Kinerja Perusahaan Perbankan - Agustin, Rina; Hotang, Keri Boru; Soleha (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2022)
The purpose of this study was to study the effect of the audit committee, the board of commissioners, and the board on the company's performance. This study uses banking companies listed on the Indonesia Stock Exchange (IDX) which are classified as LQ45 during the period 2010-2020. This research uses quantitative research methods. The research sample that was successfully obtained using the purposive sampling method and according to the criteria was 6 banking companies with a total of 66 data. The results show that the audit committee and the board of commissioners affect the company's performance, while the research board has no effect on the company's performance.